Gender differences in health-related quality of life among coronary patients and the relation with comorbidity burden. Results from the ESC EORP EUROASPIRE V survey. (14th October 2021) - Vynckier, P; Van Wilder, L; Gevaert, S; De Bacquer, D; De Smedt, D; ,
Abstract: Background: Impaired health-related quality of life (HRQoL) is related to increased morbidity and mortality among coronary heart disease (CHD) patients. Although gender differences in HRQoL have been observed in the general population, the magnitude of gender differences tends to be more pronounced in CHD patients. In addition, a higher comorbidity burden, common in CHD patients, is known to result in an even worse HRQoL outcome. Purpose: The aim of this study is to evaluate HRQoL- gender differences among CHD patients and to explore its relationship with comorbidity burden. Methods: Analyses were based on the most recent ESC EORP EUROASPIRE V survey data, including patient information from 27 European countries. Consecutive patients (18–80 years), hospitalized for a coronary event or surgical procedure were recruited in the survey. Data presented here were obtained from medical records and standardized patient interviews (6 months to 2 years following hospital discharge). Mean EQ-5D-5L index scores were used to evaluate patients' self-reported health status. A history of stroke, heart failure, peripheral artery disease (PAD), chronic kidney disease (CKD), and self-reported diabetes were considered as comorbidities. Generalized linear mixed models were fitted accounting for clustering of patients within countries and adjusted for age. To investigate the interplay of gender with comorbidities, two-way interaction terms were included. Results: Data was available for 8, 261 patients, including 25.8% women. Women were slightly older than men (65.4 vs 63.0 years) and more likely to have a history of stroke (5.3% vs. 3.7%; p=0.04), heart failure (7.6% vs. 5.9%; p=0.02), and self-reported diabetes (33.1% vs. 28.0%; p<0.001). No significant differences were seen in the prevalences of PAD (2.5% vs. 2.7%; p=0.25) and CKD (13.8% vs. 14.5%; p=0.47). Overall, women reported a worse EQ-5D-5L index score compared to men (0.73 vs. 0.81; p<0.001). Also, considering CHD patients without comorbidities, women reported a worse EQ-5D-5L index score (0.77 vs. 0.84; p<0.001). Stratification by comorbidities revealed that the EQ-5D-5L index score differed substantially between genders. Although no gender differences were found for patients with PAD (0.62 vs. 0.68; p=0.13), women reported a worse EQ-5D-5L index score if having a history of stroke (0.59 vs. 0.69; p<0.001), heart failure (0.64 vs. 0.71; p=0.01), CKD (0.76 vs. 0.81; p<0.001), and self-reported diabetes (0.69 vs. 0.78; p<0.001). Moreover, detailed analyses revealed a significant interaction between gender and self-reported diabetes (p=0.04) and gender and CKD (p=0.04) in favour of women. A closer look at the combination of comorbidities revealed no significant interactions possibly due to the smaller number of patients. Conclusion: Women reported a worse HRQoL compared to men. Further quantitative and qualitative research is needed to understand the gender-differential in HRQoL. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Fonds voor hartchirurgie - Fonds pour la Chirurgie Cardiaque